Effect of Fiber Orientation on Physical and Mechanical Properties of Typha angustifolia Natural Fiber Reinforced Composites - Bhuvaneswari, Venkateswaran; Rajeshkumar, Lakshminarasimhan; Sathishkumar, Thottyeapalayam Palanisamy; Rajeshkumar, Guruswamy; Sanjay, Mavinkere Rangappa; Siengchin, Suchart (Applied Science and Engineering Progress, 2023)
Natural fiber-reinforced polymer composites (NFRPC) are sustainable, renewable, and potential replacements in lieu of non-renewable and non-biodegradable synthetic fiber-reinforced composites. The application spectrum of natural fiber composites is widening day by day due to rigorous research carried out on these materials. Accordingly, the current study aims to determine the mechanical properties like impact and compressive strength and physical properties like water absorption behavior for Typha angustifolia (TA) fibers reinforced composites (TFRC). Composites were fabricated using the compression molding method with fibers in unidirectional (UD) and bidirectional (BD) orientation with a weight fraction of 10, 15, and 20%. X-ray diffraction studies were carried out on the fabricated composites to ascertain the presence of micro constituents. All the tests were conducted according to ASTM standards. Results indicated that 20% of TFR composites in BD orientation outperformed other composites. Failure surface morphology was analyzed using scanning electron microscopic analysis (SEM).